UI/UX Design of WeatherWise: A Mobile Weather Application using a Human-Centered Design Approach - Pattipawae, Christin; David, Felix (Sistemasi: Jurnal Sistem Informasi, 2025)
The design of User Interface (UI) and User Experience (UX) plays a crucial role in weather forecast applications, which often face issues such as unstructured layouts, inaccurate information, and delayed notifications. Using a Human-Centered Design (HCD) approach, this study aims to design the UI/UX of the WeatherWise application to enhance user comfort and satisfaction. The methodology follows the stages of inspiration, ideation, and implementation, involving data collection through observations and interviews to understand user needs, followed by prototyping for evaluation. The results are expected to produce a more intuitive and responsive design that effectively addresses existing issues, positioning WeatherWise as a more effective and preferred weather forecast application compared to others. Thus, this research not only improves the user experience in weather applications but also serves as a guide for developers in applying HCD principles to UI/UX design.